Short- and Midterm Results between Laparoscopic Roux-en-Y Gastric Bypass and Laparoscopic Sleeve Gastrectomy for the Treatment of Morbid Obesity - Bandar Albeladi; Céline Bourbao-Tournois; Noel Huten (Hindawi Limited, 2013)
Background. Laparoscopic Roux-en-Y gastric bypass (LRYGB) is one of the most widely used bariatric procedures today, and laparoscopic sleeve gastrectomy (LSG) as a single-stage procedure for the treatment of morbid obesity is becoming increasingly popular in Europe. The aim of this study was to compare short- and midterm results between LRYGB and LSG. Methods. An observational retrospective study from a database of patients undergoing LRYGB and LSG between January 2008 and June 2011. Seventy patients (mean age 39 years) were included. Patients were followed at 6, 12, and 18 months. Operative time, length of stay, weight loss, comorbidity improvement or resolution, postoperative complications, reinterventions and mortality were evaluated. Results. Thirty-six LRYGB and 34 LSG were included. Mean operative time of LSG was 106 min while LRYGB was 196 min (). Differences in length of stay, early and late complications, and improvement or resolution in comorbidities were not significant (). Eighteen months after surgery, average excess weight loss was 77.6% in LRYGB and 57.1% in LSG (). There was no surgery-related mortality. Conclusions. Both LRYGB and LSG are safe procedures that provide good results in weight loss and resolution of comorbidities at 18 months.